Italy : Financial Sector Assessment Program-Technical Note-Insurance Sector Regulation and Supervision. (IMF Staff Country Reports; Country Report ;, 2020)
This technical note (TN) provides an update and an assessment of the supervisory framework and practices for the Italian insurance sector since the last assessment concluded in 2013. The mission conducted a target review focusing on the implementation of Solvency II, the financial resilience of insurers, the effectiveness of supervision, and previously identified weaknesses without a full assessment of Italy's observance with the International Association of Insurance Supervisors (IAIS) Insurance Core Principles (ICPs). Implementation of the European Union (EU) Solvency II Directive in 2016 has significantly strengthened regulation and supervision since the last FSAP, introducing risk-based capital standards, comprehensive insurance group supervision and new requirements on governance, risk management and controls. The supervision of intermediaries has also been strengthened in line with the EU Insurance Distribution Directive in 2018.